(untitled) (Annals of Agricultural Research, 2024)
Sporulation loss over time poses a significant challenge when culturing Pyricularia oryzae on artificial media, with cultures losing their sporulation within just three to four weeks. Factors such as temperature, light, humidity, and hyphal age influence the sporulation of this pathogen. This study aimed to determine the optimal location within a culture plate to harvest bits for maximum vegetative growth and sporulation of P. oryzae while sub-culturing and mass multiplication. A total of 40 isolates (20 each from leaf and neck blast of basmati rice) were evaluated for vegetative growth and sporulation in relation to hyphal age, revealing significant variation among isolates. The oldest hyphae, located at the central 5 mm radial zone of the colony, exhibited the lowest sporulation rates (4.17 conidia/ml for leaf isolates and 3.84 conidia/ml for neck isolates) and the slowest vegetative growth rates (6.29 mm/24 hours and 6.04 mm/24 hours) respectively. In contrast, the highest sporulation was observed in colonies derived from hyphal bits taken from the radial zone 15-30 mm from the center of the colony. Moderate sporulation and vegetative growth rates were recorded from bits taken from 5-15 mm and 30-45 mm radial zones, respectively. These findings offer vital insights that enhance understanding on the fungal biology and advance both fundamental and practical research on rice bast.